Ethanol Extract of Spondias pinnata Leaves Reduce Parasite Number and Increase Macrophage Phagocytosis Capacity of Mice Infected by Plasmodium berghei - Dewa Ayu Agus Sri Laksemi; I Gusti Kamasan Arijana; I Made Sudarmaja; Ni Luh Ariwati; Ketut Tunas; Putu Ayu Asri Damayanti; Ni Luh Putu Eka Diarthini; I Kadek Swastika; Ida Ayu Dewi Wiryantini (The Prodia Education and Research Institute (PERI), 2021)
BACKGROUND: Currently, there is no vaccine against malaria in humans, the development of resistance to anti-malarial drugs, causing the need to find new alternatives to overcome malaria infections. This study aimed to determine effect of Spondias pinnata in increasing cellular immunity, especially phagocytosis activity of peritoneal macrophages against Plasmodium berghei infection.METHODS: This was an experimental study with two stages of research, each stage requires 36 Balb/c mice, aged 2 months and weight 20-25 grams. After one week of acclimatization, the mice were put into 6 different groups, each group consisted of 6 mice. The negative control was a group of mice given distilled water for 14 days then infected by P. berghei in the 15th day. Meanwhile, T1, T2, T3, T4 and T5 groups were given S. pinnata leaves ethanol extract with dose of 25, 50, 100, 200 and 400 mg/kg body weight (BW)/day, respectively, and then infected by P. berghei in the 15th day.RESULTS: The results showed that the lowest parasitemia and the highest capacity of macrophage to phagocytose latex was found in treatment group T3 that received 50 mg/kg BW of S. pinnata leaves ethanol extract. Based on analysis of the Pearson correlation test, there was a significant correlation between percent phagocytosis and parasitemia (p<0.05).CONCLUSION: Ethanol extract of S. pinnata leaves lower the parasite number of P. berghei in Balb/c mice and increase the capacity of macrophage to phagocytose latex. However, the mechanisms of how S. pinnata leaves extract in activating phagocytosis capacity and reducing parasitemia still need further investigation.KEYWORDS: phagocytosis, Plasmodium berghei, parasite number, Spondias pinnata